Association of energy source with outcomes in en bloc TURB: secondary analysis of a randomized trial - Mancon, Stefano; Soria, Francesco; Hurle, Rodolfo; Enikeev, Dmitry; Xylinas, Evanguelos; Lusuardi, Lukas; Heidenreich, Axel; Gontero, Paolo; Compérat, Eva; Shariat, Shahrokh F; D'Andrea, David; eBLOC Study Team (World journal of urology, 2025)
PURPOSE: To comprehensively evaluate the efficacy of different energy sources used for en-bloc transurethral resection of bladder tumors (ERBT) on perioperative outcomes. METHODS: This sub-analysis derived from a prospective randomized study that enrolled patients undergoing ERBT vs conventional transurethral resection of the bladder (cTURB) from January 2019 to January 2022 (NCT03718754). Endpoints were pathological specimen quality and perioperative outcomes after either monopolar (m-ERBT) or bipolar (b-ERBT) or laser (l-ERBT) ERBT. RESULTS: 237 bladder tumors resected in 188 patients included in the analyses: 29 (12.2%) m-ERBT, 136 (57.4%) b-ERBT and 72 (30.4%) l-ERBT. Detrusor muscle (DM) was detected in 191 (80.6%) specimens. Per-tumor analysis revealed comparable rate of DM in the specimens obtained via different energy modalities (p = 0.7). Operative time was longer in the l-ERBT cohort compared to m-ERBT and b-ERBT (p = 0.02) and no obturator nerve reflex (ONR) onset was reported. On logistic regression analysis, b-ERBT was associated with negative lateral resection margins (OR 2.81; 95% CI 1.02-7.70; p = 0.04). There was no significant association of the resection technique with perforation and conversion rates (all p > 0.05). Within a median follow up of 22mo (IQR 11-29), a total of 35 (18.6%) patients had a local recurrence. On Cox regression analysis, patients resected with b-ERBT were less likely to have a recurrence (HR 0.34; 95% CI 0.15-0.78; p = 0.01); When adjusting for established confounders, this association was confirmed (HR 0.24; 95% CI 0.10-0.60; p = 0.002). CONCLUSIONS: Different energy sources might achieve comparable perioperative outcomes. Further perspectives involve the assessment of long-term differential oncological outcomes associated with various energy modalities.
Keywords: výsledek terapie; Lasers, Solid-State; Male; Resection; nádory močového měchýře; En bloc; lasery pevnolátkové; laserová terapie; Aged; Prospective Studies; Bladder cancer; mužské pohlaví; senioři; Laser Therapy; Diagnosis; Treatment; Treatment Outcome; lidé; ženské pohlaví; Humans; Cystectomy; Energy source; cystektomie; Urinary Bladder Neoplasms; Female; lidé středního věku; Middle Aged; prospektivní studie